Non-Economic Functions in Education Investment - Amarta, Yoga; Nella, Nella; Arina, Yudela; Yahya, Yahya; Hadiyanto, Hadiyanto (Postgraduate School, Universitas Negeri Padang, 2023)
Education plays an important role in improving the standard of living and the quality of the human economy. This causes many people to think that higher education will provide high economic returns. But in reality, many graduates have completed their education at tertiary institutions, but are still unemployed, so people think that it is useless to go to school or have a higher education. Even though the function of investment in education is not only an economic function. This study uses literature studies by analyzing books, journals, or research related to the problem. From the results of the analysis, education has several aspects of non-economic functions such as religious, social, political and legal, cultural, educational, health, and social life functions. This shows that the return value from investment in education is not only an economic aspect, but includes many aspects. Education helps people to become more socially, politically, and culturally aware and better equipped to understand and apply science and technology to advance human civilization.